The Limits of the Declaratory Judgment - Malcolm Rowe, Justice; Shnier, Diane (McGill Law Journal, 2022)
A declaratory judgment is a determination of rights without consequential relief. Declaratory judgments can be highly useful for litigants, but they are also somewhat lacking in doctrinal clarity, raising a number of questions that go to the core of the judicial role. What does it mean to have a legal right, or to declare the existence of a legal right, if that right, while recognized, is not enforced? It has been held that a declaratory judgment is available only when there is a real dispute between the parties, but what is a real legal dispute without legal rights that can be enforced? When is it the business of courts to declare the existence of such a right?